2020
DOI: 10.1038/s42003-020-1067-1
|View full text |Cite
|
Sign up to set email alerts
|

Geometric regulation of histone state directs melanoma reprogramming

Abstract: Malignant melanoma displays a high degree of cellular plasticity during disease progression. Signals in the tumor microenvironment are believed to influence melanoma plasticity through changes in the epigenetic state to guide dynamic differentiation and de-differentiation. Here we uncover a relationship between geometric features at perimeter regions of melanoma aggregates, and reprogramming to a stem cell-like state through histone marks H3K4Me2 and H3K9Ac. Using an in vitro tumor microengineering approach, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…Melanoma CSCs are associated with a spectrum of markers and molecular pathways which provide them different advantages [5,190,[192][193][194][195][196][197][198][199][200][201][202][203][204][205], though they may represent targets for the development of new therapies (Table 5). ABC transporters-ATP-binding cassette transporters; ABCB5-ABC sub-family B member 5; ABCC1 ABC subfamily C member 1; ABCC2-ABC sub-family C member 2; ABCC6-ABC sub-family C member 6; ABCG2-ABC sub-family G member 2; ALCAM-activated leukocyte cell adhesion molecule; ALDH-aldehyde dehydrogenase; Ang1/2-angiopoietin 1/2; Bcl-2-B-cell lymphoma 2; BCRP-breast cancer resistant protein; CD-cluster of differentiation; c-KIT-mast/stem cell growth factor receptor kit; CSC-cancer stem cell; CTLA-4-cytotoxic T lymphocyte antigen-4; CXCR6-C-X-C Motif Chemokine Receptor 6; DDX3X-DEAD-Box Helicase 3 X-Linked; DOCK 2-dedicator of cytokinesis 2; EGFR-epidermal growth factor receptor; EIF3H-eukaryotic translation initiation factor 3 subunit H; EMT-epithelial-mesenchymal transition; EZH2-enhancer of zeste homolog 2; GLI-Hh/Glimo; H3K27me2/3-trimethylates lysine 27 of histone H2/3; H3K9-histone H3 lysine 9 acetylation; HIF-1-hypoxia inducible factor 1; HNK-1-human natural killer 1; hnRNP-heterogeneous ribonucleoproteins; hTERT-human telomerase reverse transcriptase; ICAM-1-intercellular adhesion molecule 1; JARID1B-lysinespecific demethylase 5B; L1CAM-L1 adhesion molecular; MAPK-mitogen-activated protein kinase; MCAMmelanoma cell adhesion molecule; MDR1-multidrug-resistance gene product 1; miR-microRNA gene; MS4A1membrane spanning 4-domains A1; NGFR-nerve growth factor receptor; Notch4-Notch Receptor 4; PD-1programmed cell death protein 1; PDL-1-programmed death-ligand 1; RANK-receptor activator of NF-κB; Snail-Zinc finger protein SNAI1; SOX-SRY-Box transcription factor 2; Tie2-tyrosine-protein kinase receptor Tie-2; TPPP3-tubulin polymerization promoting protein family member 3; VEGF-vascular endothelial growth factor; VEGFR 1/2-vascular endothelial growth factor receptor 1/2.…”
Section: Melanoma Cscs-the Origin Of Heterogeneity Plasticity Aggress...mentioning
confidence: 99%
See 1 more Smart Citation
“…Melanoma CSCs are associated with a spectrum of markers and molecular pathways which provide them different advantages [5,190,[192][193][194][195][196][197][198][199][200][201][202][203][204][205], though they may represent targets for the development of new therapies (Table 5). ABC transporters-ATP-binding cassette transporters; ABCB5-ABC sub-family B member 5; ABCC1 ABC subfamily C member 1; ABCC2-ABC sub-family C member 2; ABCC6-ABC sub-family C member 6; ABCG2-ABC sub-family G member 2; ALCAM-activated leukocyte cell adhesion molecule; ALDH-aldehyde dehydrogenase; Ang1/2-angiopoietin 1/2; Bcl-2-B-cell lymphoma 2; BCRP-breast cancer resistant protein; CD-cluster of differentiation; c-KIT-mast/stem cell growth factor receptor kit; CSC-cancer stem cell; CTLA-4-cytotoxic T lymphocyte antigen-4; CXCR6-C-X-C Motif Chemokine Receptor 6; DDX3X-DEAD-Box Helicase 3 X-Linked; DOCK 2-dedicator of cytokinesis 2; EGFR-epidermal growth factor receptor; EIF3H-eukaryotic translation initiation factor 3 subunit H; EMT-epithelial-mesenchymal transition; EZH2-enhancer of zeste homolog 2; GLI-Hh/Glimo; H3K27me2/3-trimethylates lysine 27 of histone H2/3; H3K9-histone H3 lysine 9 acetylation; HIF-1-hypoxia inducible factor 1; HNK-1-human natural killer 1; hnRNP-heterogeneous ribonucleoproteins; hTERT-human telomerase reverse transcriptase; ICAM-1-intercellular adhesion molecule 1; JARID1B-lysinespecific demethylase 5B; L1CAM-L1 adhesion molecular; MAPK-mitogen-activated protein kinase; MCAMmelanoma cell adhesion molecule; MDR1-multidrug-resistance gene product 1; miR-microRNA gene; MS4A1membrane spanning 4-domains A1; NGFR-nerve growth factor receptor; Notch4-Notch Receptor 4; PD-1programmed cell death protein 1; PDL-1-programmed death-ligand 1; RANK-receptor activator of NF-κB; Snail-Zinc finger protein SNAI1; SOX-SRY-Box transcription factor 2; Tie2-tyrosine-protein kinase receptor Tie-2; TPPP3-tubulin polymerization promoting protein family member 3; VEGF-vascular endothelial growth factor; VEGFR 1/2-vascular endothelial growth factor receptor 1/2.…”
Section: Melanoma Cscs-the Origin Of Heterogeneity Plasticity Aggress...mentioning
confidence: 99%
“…Melanoma CSCs are associated with a spectrum of markers and molecular pathways which provide them different advantages [ 5 , 190 , 192 , 193 , 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 ], though they may represent targets for the development of new therapies ( Table 5 ).…”
Section: Melanoma Cscs—the Origin Of Heterogeneity Plasticity Aggress...mentioning
confidence: 99%
“…Through an in vitro tumor, microengineering approach, authors demonstrated that stress exerted on melanoma aggregate perimeters could determine the cellular phenotypic transition into a stem cell-like melanoma-initiating cell (MIC) state. In this work, H3K9ac and H3K4me2 histone modifications and the enrichment of epigenetic modifier PR domain zinc finger 14 (PRDM14) were correlated to stemness, suggesting their role in cellular plasticity and tumorigenicity [72].…”
Section: Chromatin Remodelingmentioning
confidence: 63%
“…Signals produced by the TME can also influence melanoma plasticity through changes in the epigenetic state to force dynamic differentiation and de-differentiation. The microenvironment-mediated epigenetic regulation of gene expression includes stress signals like pH, hypoxia, radiation, stiffness, as well as interfacial stress, which constrain a conversion of melanoma cell to a stem cell-like phenotype (Lee et al 2020 ). The hypothesis of the occurrence of MTSC (melanoma tumor stem cells) presenting the CD 271 (neurotrophin receptor) antigen, responsible for metastasis occurring, has been thoroughly verified (Boiko et al 2010 ).…”
Section: General Differences Between Melanocytes and Melanoma Cellsmentioning
confidence: 99%